Identifying the Dominant Ecological Worldviews of Community Leaders and the Influences These Have in Managing Conservation Areas in Ghana - Owusu-Ansah, Nana (Archīum Ateneo, 2021)
This study was set on the premise of a research question that sought to identify the dominant ecological worldviews of Community Resources Management Area (CREMA) leaders and the influences these have on the management prescriptions of their conservation areas. The relevance of the question was to identify whether the CREMA leaders subscribed to an eco-centric or an anthropocentric worldview which could have direct consequences for the control of resource levels of utilization after the devolution of authority. A phenomenological approach was thus applied to collect data from nine selected conservation leaders from three different CREMAs. Their ecological worldviews were found to be mixed—depending on the ecological worldview domain, the CREMA leaders showed leanings toward stances ranging from complete eco-centrism to ambivalent eco-centrism and ambivalent anthropocentrism. The findings, however, mostly suggested that the dominant ecological worldviews of the CREMA leaders were eco-centric and not anthropocentric. They exercised the middle ground, i.e., ambivalent ecological worldviews stances, to influence sustainable natural resource utilization while complete eco-centric worldviews were applied to protect balances in ecological functions. The leaders applied these determinations to promote the dual purposes of the CREMAs as they were set up for nature conservation and socio-economic development in Ghana. The study also recommends that the findings should be explored further to develop adaptable criteria that include ecological worldviews in the selection of CREMA leaders.